Влияние квертулина на состояние печени крыс с преднизолоновым иммунодефицитом - Васюк, В.Л.; Левицкий, А.П.; Гоженко, А.И. (Актуальні проблеми транспортної медицини, 2014)
Введение преднизолона снижает содержание в крови лимфоцитов, а в печени уровень лизоцима при увеличении активности уреазы, степени дисбиоза, уровня маркеров воспаления. В сыворотке крови увеличивается содержание билирубина и активность АЛТ. Введение квертулина оказывает гепатопротекторный эффект. Введення преднізолона знижує вміст в крові лімфоцитів, а в печінці рівень лізоцима при збільшенні активності уреази, ступеня дисбіозу, рівня маркерів запалення. В сироватці крові зростає вміст білірубіна і активність АЛТ. Введення квертуліна справляє гепатопротекторний ефект. Objective: To determine the hepatoprotective effect of kvertulina in experimental prednisolone immunodeficiency (PI). Materials and methods. PI was reproduced in rats by oral administration of prednisolone at a dose of 5 mg / kg. Status of РI was evaluated by the content of lymphocytes and lysozyme activity. Liver state was evaluated by level of ALT and bilirubin in serum as well as activity of elastase, urease, lysozyme, catalase, and the MDA content in liver tissue. Kvertulin was administered in the feed at a dose of 400 mg / kg for 14 days. Results. The application of prednisolone reduces the amount of blood lymphocytes 3 times, lysozyme activity in liver 1.9 times and nearly to 3 times increases in the degree of liver dysbiosis. Experiencing increasing levels of inflammatory markers in the liver (elastase, MDA), bilirubin and ALT in blood serum. The application of kvertulina reduces the degree of PI, dysbiosis and occurrences of hepatitis. Conclusion. Kvertulin has hepatoprotective effect in immunodeficiency.